Theoretical statements for synthesis of conjugate couplings - P. D. Balakin; V. N. Belkov (Омский научный вестник)
The conditions for the synthesis of conjugate couplings are systematized on the basis of a single geometric-kinematic criterion, which consists in the equality of the velocity projections of the points of the active surfaces that make up the higher pair on the common contact-normal to these surfaces. The technology of formation of a family of conjugate couplings by a two — parameter envelope by an involute helicoid or its particular varieties-a circular cone or plane-is theoretically justified.